2013
DOI: 10.5483/bmbrep.2013.46.8.075
|View full text |Cite
|
Sign up to set email alerts
|

The uniqueness of the plant mitochondrial potassium channel

Abstract: The ATP-inhibited Plant Mitochondrial K+ Channel (PmitoKATP) was discovered about fifteen years ago in Durum Wheat Mitochondria (DWM). PmitoKATP catalyses the electrophoretic K+ uniport through the inner mitochondrial membrane; moreover, the co-operation between PmitoKATP and +/H+ antiporter allows such a great operation of a K+ cycle to collapse mitochondrial membrane potential (ΔΨ) and ΔpH, thus impairing protonmotive force (Δp). A possible physiological role of such ΔΨ control is the restriction of harmful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…As a consequence, passive anion transport across the inner mitochondrial membrane may shift from the energy-dependent anion carriers toward the electrophoretic flux through the PIMAC. Results from in vitro studies on DWM are in line with this picture [10,11,19], with the notable exception of AAC function. Both ADP and ATP are not transported by PIMAC, moreover, in de-energized DWMthe ADP/ATP exchange is inhibited by oligomycin, a powerful AAC inhibitor, thus suggesting AAC operation in the absence of measurableΔΨ, the driving force for AAC.…”
Section: Plant Inner Membrane Anion Channel (Pimac) Carriers and Anisupporting
confidence: 72%
See 2 more Smart Citations
“…As a consequence, passive anion transport across the inner mitochondrial membrane may shift from the energy-dependent anion carriers toward the electrophoretic flux through the PIMAC. Results from in vitro studies on DWM are in line with this picture [10,11,19], with the notable exception of AAC function. Both ADP and ATP are not transported by PIMAC, moreover, in de-energized DWMthe ADP/ATP exchange is inhibited by oligomycin, a powerful AAC inhibitor, thus suggesting AAC operation in the absence of measurableΔΨ, the driving force for AAC.…”
Section: Plant Inner Membrane Anion Channel (Pimac) Carriers and Anisupporting
confidence: 72%
“…This occurs in a KCl medium able to activate the ATP-sensitive mitochondrial potassium channel (PmitoKATP); under this particular condition, the massive K+ uptake by DWM may strongly decreaseΔΨ without compensation due to ΔpH increase, thus collapsing pmf [9,10]. A possible mechanism explaining this unexpected ATP synthesis has been recently reported [11], but another point remains still unsolved regarding the transport of metabolites: to synthesize ATP via OXPHOS it is necessary to carry out uptake of succinate, Inorganic Phosphate (Pi) and ADP as well as to release the newly synthesized ATPoutside DWM. Since the force driving these transports should derive from ΔΨ and ΔpH, the question arises about how these movements of metabolites may be possiblein the absence of pmf in this in vitro model system.…”
Section: Editorialmentioning
confidence: 97%
See 1 more Smart Citation
“…A mitochondria‐localized K + channel (mitoK ATP channel) has also been isolated as a K + uniporter (Pastore et al , , ). It has been indicated that K + concentrations in the mitochondrial matrix are regulated by the mitoK ATP channel and subsequent K + entry into the mitochondria results in depolarization of the membrane (Jarmuszkiewicz et al ).…”
Section: Potassium Sensing and Transport In Plantsmentioning
confidence: 99%
“…On the other hand, in the presence of KCl and ATP, a PmitoK ATP activity exists, but it is inhibited, thus reducing the whole rate of the K + cycle; so, a “controlled collapse” is achieved that avoids complete uncoupling. In particular, this ATP-braked activity of PmitoK ATP may strongly reduce the classically detectable bulk phase Δp, but in such a manner to only partially subtract protons to ATP synthase and to retain a latent proton movement, able to sustain ATP synthesis and transport ( Pastore et al, 2013 ; Trono et al, 2014 ; Figure 3B ). Consistently, in the presence of valinomycin, the ATP brake of PmitoK ATP activity is overcome, so exacerbating K + cycle; under this condition, complete uncoupling occurs, preventing ATP synthesis (Figure 3C ).…”
Section: Effect Of Pmitok Atp Modulation On Mitochmentioning
confidence: 99%